Thyroid dysfunction in elderly first-episode drug-naïve major depressive disorder patients with comorbid dyslipidemia: prevalence, clinical profile and associated factors - Song, Xiuhua; Yi, Lei; Wang, Shenghai; Zhang, Xiangyang (Frontiers in Psychiatry, 2026)
BackgroundElderly major depressive disorder (MDD) patients often exhibit complex symptomatology and high rates of abnormal lipid metabolism (ALM), yet predictors of abnormal thyroid function in those with co-occurring lipid metabolism are not fully elucidated. This study aimed to investigate the relationship between thyroid function and ALM in first-episode, drug-naïve (FEDN) elderly MDD patients.Methods1,029 elderly FEDN MDD patients were enrolled. Demographics, lipid profile (TC, TG, LDL-C, HDL-C), thyroid parameters (TSH, FT3, FT4, TG-Ab, TPO-Ab), and symptom ratings (HAMD, HAMA, PANSS-positive) were assessed.ResultsPrevalence of abnormal thyroid function was 69.0%. Compared with ALM patients without thyroid dysfunction, those affected had higher HAMD, HAMA, and PANSS-positive scores, more suicide attempts, severe anxiety, and psychotic symptoms (all P < 0.05). Logistic regression identified BMI (OR = 1.186), HAMD score (OR = 1.201), blood glucose (OR = 4.03), TC (OR = 1.683), and LDL-C (OR = 1.299) were independent associated factors for abnormal thyroid function in MDD patients with comorbid ALM(all P < 0.001).ConclusionAbnormal thyroid function is highly prevalent in elderly FEDN MDD patients with ALM; clinical severity, glucose, and lipid levels contribute to this comorbidity. These findings suggest that elderly, first-episode MDD patients with dyslipidemia, particularly those with elevated BMI, high blood glucose, and severe depressive symptoms, should undergo routine screening for thyroid dysfunction to facilitate early intervention.